If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4j + -3j = 0 Combine like terms: 4j + -3j = 1j 1j = 0 Solving 1j = 0 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Divide each side by '1'. j = 0 Simplifying j = 0
| (n+4)*9=72 | | 4s-13=15 | | (n-7)*3=12 | | 42x+3=43x | | (n+2)*5=20 | | 7x-1=3(x+2) | | 4a-1a=4 | | 4a-1a=4# | | 4-3(x+1)=10 | | 31x+4=128 | | -2(-x-4)=-2x+4 | | 9-3(2+y)=9 | | 8(4+y)=7(y-6) | | x+106=100 | | 260-5X=40X+20 | | p-2p=18 | | x^2-10x=-8 | | 1.005xn=2 | | 3x+2=-2x-28 | | 6(c+1)=5+5c | | 4(2x+3)=3x-(2x-2) | | 10(3-x)=-4x-6 | | 2a+8=54 | | -12=-5-6x+11 | | D+-8d+7=0 | | 2x+12+6x-10=180 | | -0.06y+0.08(1100-y)=0.36y | | 8x+12=9x+5 | | -5a-5(1-4a)=-5+4a | | 2(4+x)=4x+3 | | 5x-16=4x+7 | | 4x+3x=6x-6 |